Looking into historical cracks analysing repaired silver objects by electron microscopy - Tissot, Isabel (2022)
ABSTRACT: The identification of structural alterations of silver alloy objects of cultural interest is essential to assess their state of conservation and define maintenance programmes. Alterations induced by previous repair and cleaning actions strongly affect the conservation condition, influencing the type and extension of conservation procedures. The detailed analysis of ancient repairs is a subject to be investigated. In this work, we show the potentialities of scanning electron microscopy in the characterisation of structural repairs and their influence on the conservation state of silver objects. The study of distinct silver objects dated to the 16th and 18th centuries allowed us to show, among others, the non-intentional dealloying of copper due to the use of acid solutions in surface cleanings and cracks resulting from incorrect handling. The data collected by microscopic examination contributed to the definition of preservation and maintenance methodologies applied to those silver objects.